DIGITAL MARKETING IN ONLINE MARKETING CONCEPT: AD CONTENT SELECTION STRATEGY, AD BUDGETING, AND AD POSTING TIME - Justine; Frederic; David Tenggara; Hendra Jonathan Sibarani; Aisyah (ZILLZELL MEDIA PRIMA, 2024)
Digital marketing is very important to apply in developing a marketing concept that uses an online system by providing an application that supports the process of selling and marketing products. Some of the things that become the assessment of online application users are the advertisements displayed that provide information that supports the needs of the community in general, because not all people are digital savvy and understand the information conveyed from advertisements displayed either through internet media, television, or bill boards. The research objective is to test and analyse the effect of ad content selection strategy, ad budgeting, and ad posting time on the use of digital marketing in the online marketing concept. This study uses a quantitative approach and tests the research hypothesis using smartpls. The research population is respondents who are in Medan - Deli District in 2022, with total population of 192,933 people using the slovin formula, a sample size of 100 respondents is obtained, where the sampling technique uses simple random sampling. The research results obtained that partially the variables of ad content selection strategy, ad budgeting and ad posting time have a positive and significant effect on the use of digital marketing in the concept of online marketing, while simultaneously the variables of ad content selection strategy, ad budgeting, and ad posting time have a positive and significant effect on the use of digital marketing in the concept of online marketing. This proves that the use of digital marketing has a huge impact on marketing and increasing product sales.